Manual de procedimientos para la mejora de procesos en áreas de recepción y ama de llaves del Hotel Poseidón, Manta. - Intriago Mieles, Cesar Patricio (2018)
The objective of this research is to prepare a procedures manual for the reception and housekeeping areas, Poseidón hotel in Manta canton. The compiled information was obtained through bibliographic review and field work, being an exploratory-descriptive investigation. Regarding the results, in the first phase the characteristics of the Hotel were characterized, identifying the structure of the organizational charts by areas and the non-structuring of departmental objectives. The second phase was established through the situational diagnosis by areas, applying tools such as internal analysis matrices and the SWOT matrix, allowing to identify problems, such as the non-standardization of computer processes that help improve the information process, in addition to there is limited interdepartmental communication; industrial safety, addressed to the internal client at the time of cleaning the rooms; the work performance of the employees was determined, analyzing gaps based on the quality of the service, supporting deficiencies, due to not knowing in all cases what the client expects and not selecting the design nor the standards of the correct service. In the third phase of the manual design, it was necessary to review hotel management documents such as the INEN standards, the hospitality and technical standard management system, for the design and structuring of the cards and flowcharts. In conclusion it was evidenced the non-existence structures that allow the activities organization and processes in the reception and housekeeper areas of the Poseidon hotel.